Sobolev space estimates for solutions of the equation ∂¯u=f on polycylinders - Patrick W. Darko; Clement H. Lutterodt (International Journal of Mathematics and Mathematical Sciences)
In trying to improve Weinstock's results on approximation by holomorphic functions on certain product domains, we are led to estimates in Sobolev spaces for the ∂¯-operator on polycylinders for (γ,q)-forms. This generalizes our results for the same operator on polycylinders previously obtained, and can be applied to a number of other problems such as the Corona problem.